Margaret Mead’s Coming of Age in Ethnography: Storying Scientific Adventure in the South Seas - McLeod, Jacqueline (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2010)
A lightening rod for an array of criticism, Coming of Age in Samoa also attained monumental popularity with both scholarly and popular reading audiences, convincing many that it captured the sexual and social lives of Samoan adolescent girls and that North American girls might be instructed by this portrait. Taking a “recovery and reappraisal” approach, this article argues that the text is neither a collection of detailed, field note-anchored observations nor a cross cultural critique, but a love story to place. The text has much in common with postmodern conceptions of ethnography, which acknowledge “writing culture” as mediated by interpretive, representational and linguistic considerations. Like many postmodern ethnographers, Mead self-consciously constructs an authorial position rather than attempting to remain absent and objective. Part of the persona she constructs is that she is a scientist sharing data; yet she no sooner invokes standards of scientific rigor than she shifts course to promise us a good “tale”. If contemporary readers can read the text through a postmodern lens, when she wrote, her approach was unprecedented. Her awareness of transgressing scientific method emerges in the “Introduction” to the book, where she self-reflects on her decisions about authorship as performance and text as storied, artful and intimate.